2020
DOI: 10.1002/cam4.3044
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 18F‐fluorodeoxyglucose positron emission tomography/computed tomography for predicting the prognosis and treatment response of neoadjuvant therapy for pancreatic ductal adenocarcinoma

Abstract: Background The Response Evaluation Criteria in Solid Tumors (RECIST) for computed tomography (CT) is preoperatively used to evaluate therapeutic effects. However, it does not reflect the pathological treatment response (PTR) of pancreatic ductal adenocarcinoma (PDAC). The Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) for positron emission tomography (PET)/CT is effective in other cancers. This study aimed to confirm the usefulness of PERCIST and the prognostic utility of PET/CT for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In other words, PERCIST appears to increase the chances of detecting patients with progressive disease. Yokose et al [ 16 ] also aimed to confirm the usefulness of PERCIST for assessing the effect of treatment based on the pathological response to treatment, and to examine the prognostic utility of FDG PET/CT parameters. They confirmed that PERCIST and SUV max were superior to RECIST for the purpose of assessing the effects of preoperative treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, PERCIST appears to increase the chances of detecting patients with progressive disease. Yokose et al [ 16 ] also aimed to confirm the usefulness of PERCIST for assessing the effect of treatment based on the pathological response to treatment, and to examine the prognostic utility of FDG PET/CT parameters. They confirmed that PERCIST and SUV max were superior to RECIST for the purpose of assessing the effects of preoperative treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The complete resection (R0) rate ranged between 64 and 100% of the population studied. The rate of responders to neoadjuvant therapy exceeded 50% in 5 studies [ 8 , 9 , 11 , 16 , 17 ]. Based on a semiquantitative score (the RI), the consistency between histopathology and FDG PET data was reportedly in the ranges of 67–93% for responders, and 53–74% for non-responders.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the pre-treatment SUVmax cut-off value of 7.5 on PET/CT could accurately predict the OS. The results from Yokose et al [ 56 ] showed that PET response criteria in solid tumor was more accurate in determining the NAT effects for PDAC than RECIST criteria (72.7% vs 36.4%), which puts forward a new direction for future research in this field.…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%
“…Over the past 20 years, studies have shown the potential of 18 F-FDG PET/CT in the diagnosis, staging, and recurrence of PDAC [12]. 18 F-FDG PET/CT parameters, including standardized uptake value (SUV), metabolic tumor volume (MTV), and total lesion glycolysis (TLG), have been reported as prognostic factors for pancreatic cancer [13][14][15]. However, established 18 F-FDG PET/CT parameters are difficult to assess the histopathological differentiation of tumor [16].…”
Section: Introductionmentioning
confidence: 99%